Resin composition for cards or passports, film for cards or passports, cards, and passports

The resin composition for cards and passports, featuring a high glass transition temperature polyester resin and an impact-resistant modifier, addresses the challenges of low-temperature fusion, heat resistance, and solvent resistance, resulting in improved durability and reliability.

JP7647301B2Active Publication Date: 2025-03-18MITSUBISHI CHEM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021076860
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-28
Publication Date
2025-03-18
Estimated Expiration
2041-04-28

AI Technical Summary

Technical Problem

Existing resin compositions for cards and passports face challenges in achieving low-temperature fusion properties, heat resistance, solvent resistance, and durability, particularly when combining different resin sheets like polyester and aromatic polycarbonate.

Method used

A resin composition incorporating a specific polyester resin (A) with a glass transition temperature of 90° C. or higher, combined with an impact-resistant modifier, such as a core-shell type elastomer, to enhance low-temperature fusion resistance, heat resistance, and solvent resistance.

Benefits of technology

The proposed resin composition improves the durability and reliability of cards and passports by enhancing low-temperature fusion resistance, heat resistance, and solvent resistance, while maintaining dimensional stability and preventing warping.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647301000002
    Figure 0007647301000002
  • Figure 0007647301000003
    Figure 0007647301000003
  • Figure 0007647301000001
    Figure 0007647301000001
Patent Text Reader

Abstract

To provide a resin composition for cards or passports that has improved low-temperature fusibility, thermostability, and solvent resistance, while having improved durability, offering improved reliability for long-term use.SOLUTION: A resin composition for cards or passports contains a resin component containing a polyester resin (A) and an impact-resistance improver. The polyester resin (A) has a glass transition temperature of 90°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition for cards or passports, a film for cards or passports, a card, and a passport. [Background technology]

[0002] Cards such as credit cards, cash cards, ID cards, tag cards, and insurance cards are generally manufactured by stacking a plurality of resin sheets, heat fusing them, and punching them. Similarly, passports are generally manufactured by stacking a plurality of resin sheets. In the resin sheets used for cards or passports, thermoplastic resin compositions containing polyester, aromatic polycarbonate, and the like are often used as the resin component.

[0003] For example, Patent Document 1 discloses a thermoplastic resin composition for cards, which is a mixture of one or more thermoplastic resins selected from polyesters and aromatic polycarbonates and an inorganic plate-like filler. In Patent Document 1, the polyesters used include those in which the glycol units are ethylene glycol units (I) and 1,4-cyclohexanedimethanol units (II) in a molar ratio (I) / (II) of 70 / 30, and those in which the ethylene glycol units (I) and 1,4-cyclohexanedimethanol units (II) in a molar ratio (I) / (II) of 35 / 65. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-001607 Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, when manufacturing a card or passport by heat fusing a plurality of resin sheets, low-temperature fusion properties that enable heat fusing at low temperatures are sometimes required. In addition, the resin sheet requires solvent resistance because an adhesive is required when the resin sheet has poor heat fusing properties with other sheets, and the resin sheet comes into contact with ink when the resin sheet has an image-receiving layer used for printing face photographs or the like, or when the resin sheet is printed with designs or security marks.

[0006] However, when aromatic polycarbonate is used as a resin component, it is difficult to improve low-temperature fusion properties and solvent resistance. On the other hand, the polyester used in Patent Document 1 has good low-temperature fusion properties, but does not have sufficient heat resistance, and a sheet formed from the polyester has a large thermal expansion rate. Therefore, when a sheet formed from polyester is laminated with a highly heat-resistant sheet, such as an aromatic polycarbonate sheet, to produce a card or passport, problems such as large dimensional changes, poor workability, and warping of the completed card or passport may occur. Furthermore, the solvent resistance may be insufficient.

[0007] Furthermore, cards or passports using polyester films can suffer from defects such as cracks when bent during actual use or when subjected to external impacts, and may not be sufficiently reliable for long-term use.

[0008] Therefore, an object of the present invention is to provide a resin composition for cards or passports that has good low-temperature fusion properties, heat resistance, and solvent resistance while also increasing durability and improving reliability over long-term use. [Means for solving the problem]

[0009] As a result of extensive investigations, the present inventors have found that the above problems can be solved by using a specific polyester resin (A) and an impact resistance improver, and have completed the present invention as described below. That is, the present invention provides the following items [1] to

[15] . [1] A resin composition containing a resin component including a polyester resin (A) and an impact resistance improver, A resin composition for cards or passports, wherein the polyester resin (A) has a glass transition temperature of 90°C or higher. [2] The resin composition for cards or passports according to the above [1], wherein the polyester resin (A) contains a structural unit derived from a chain dihydroxy compound. [3] Storage modulus at 90°C is 3×10 7 The resin composition for cards or passports according to the above [1] or [2], having a viscosity of 1 Pa or more. [4] The resin composition for cards or passports according to any one of the above [1] to [3], wherein the polyester resin (A) contains a structural unit derived from an alicyclic dihydroxy compound. [5] The resin composition for cards or passports according to [4] above, comprising a polyester resin in which the proportion of structural units derived from the alicyclic dihydroxy compound is more than 65 mol % out of a total of 100 mol % of structural units derived from the chain dihydroxy compound and structural units derived from the alicyclic dihydroxy compound. [6] The resin composition for cards or passports according to any one of the above [1] to [5], wherein the polyester resin (A) contains a structural unit derived from ethylene glycol and a structural unit derived from cyclohexanedimethanol. [7] The resin composition for cards or passports according to any one of the above [1] to [6], wherein the polyester resin (A) contains a structural unit derived from ethylene glycol, a structural unit derived from cyclohexanedimethanol, and a structural unit derived from tetramethylcyclobutanediol. [8] The resin composition for cards or passports according to any one of the above [1] to [7], wherein the impact resistance improver is a core-shell type elastomer. [9] The resin composition for cards or passports described in [8] above, wherein the core of the core-shell elastomer contains at least one rubber selected from the group consisting of butadiene-based rubber, acrylic-based rubber, silicone-based rubber, and silicone-acrylic hybrid rubber.

[10] The resin composition for cards or passports according to any one of the above [1] to [9], wherein the content of the impact resistance improver is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the resin component.

[11] The resin composition for cards or passports according to any one of the above [1] to

[10] , which contains recycled materials.

[12] A film for cards or passports, comprising the resin composition according to any one of [1] to

[11] above.

[13] A card comprising the film described in

[12] above.

[14] A passport comprising the film described in

[12] above.

[15] A method for producing a resin composition according to any one of the above [1] to

[11] , comprising blending a recycled raw material with the resin composition. Effect of the Invention

[0010] The present invention can provide a resin composition for cards or passports that has good low-temperature fusion properties, heat resistance, and solvent resistance while also having improved durability and improved reliability for long-term use. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram showing a layer structure of a card. [Diagram 2] FIG. 2 is a schematic diagram showing a layer structure of a passport. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below with reference to the embodiments. However, the present invention is not limited to the embodiments described below. In addition, the terms "film" and "sheet" used in the following description are not clearly distinguished from each other, and the term "film" includes the term "sheet", and the term "sheet" includes the term "film".

[0013] <Resin composition for cards or passports> The resin composition of the present invention is a resin composition for cards or passports, and contains a resin component including a polyester resin (A) and an impact resistance improver.

[0014] [Polyester resin (A)] As the polyester resin (A), a polyester resin having a glass transition temperature of 90°C or higher is used. Since the polyester resin (A) has a glass transition temperature of 90°C or higher, the heat resistance is high, and the dimensional change when a film formed from the resin composition is heated is small. Therefore, the workability when producing a card or passport is improved, and furthermore, the produced card or passport is less likely to warp. In addition, the impact resistance is improved, and the reliability in long-term use is also likely to be improved. Furthermore, the resin composition containing the polyester resin (A) is likely to have good solvent resistance.

[0015] The polyester resin (A) is a polyester obtained by polycondensation of a dicarboxylic acid and a dihydroxy compound. As the dicarboxylic acid, a dicarboxylic acid derivative such as an ester or an acid halide of the dicarboxylic acid may be used for the synthesis of the polyester resin (A). From the viewpoint of heat resistance, it is preferable to use an aromatic dicarboxylic acid as the dicarboxylic acid used to obtain the polyester resin (A), and therefore it is preferable that the polyester resin (A) contains structural units derived from an aromatic dicarboxylic acid. The aromatic dicarboxylic acid is not particularly limited, and examples thereof include terephthalic acid, isophthalic acid, naphthalene-1,4-dicarboxylic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, naphthalene-1,5-dicarboxylic acid, anthracene dicarboxylic acid, 4,4'-diphenyl dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-sulfoisophthalic acid, sodium 3-sulfoisophthalate, 2-chloroterephthalic acid, 2,5-dichloroterephthalic acid, and 2-methylterephthalic acid. Of these, terephthalic acid and isophthalic acid are preferred, and terephthalic acid is more preferred from the viewpoint of transparency. The aromatic dicarboxylic acids may be used alone or in combination of two or more.

[0016] The polyester resin (A) may also contain a small amount of structural units derived from an aliphatic dicarboxylic acid (usually 40 mol% or less, for example 30 mol% or less, preferably 20 mol% or less). The aliphatic dicarboxylic acid is not particularly limited, and examples thereof include oxalic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, sebacic acid, azelaic acid, dodecanedioic acid, dimer acid, 1,3 or 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, and 4,4'-dicyclohexyldicarboxylic acid. The aliphatic dicarboxylic acid may be used alone or in combination of two or more.

[0017] The aromatic dicarboxylic acid-derived structural unit is preferably contained in the dicarboxylic acid-derived structural unit in the polyester resin (A) at 80 mol % or more, more preferably at 90 mol % or more. The upper limit is not particularly limited as long as it is 100 mol % or less, and most preferably 100 mol %.

[0018] The polyester resin (A) preferably contains a structural unit derived from a chain dihydroxy compound. By containing a structural unit derived from a chain dihydroxy compound, the polyester resin (A) tends to have good low-temperature fusion properties.

[0019] The chain dihydroxy compound used in the polyester resin (A) may be linear or may have a branched structure. Specific examples of the chain dihydroxy compound include chain dihydroxy compounds having about 2 to 18 carbon atoms, such as ethylene glycol (EG), diethylene glycol, 1,2-propylene glycol, 1,3-propanediol, 2,2-dimethyl-1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, triethylene glycol, 1,2-hexadecanediol, and 1,18-octadecanediol, and polyglycols, such as polytetramethylene ether glycol, polypropylene glycol, and polyethylene glycol. Among these, a chain dihydroxy compound having 2 to 12 carbon atoms is preferred, and one or more selected from ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol are more preferred, with ethylene glycol (EG) being particularly preferred. The chain dihydroxy compound may be used alone or in combination of two or more kinds.

[0020] The polyester resin (A) preferably has a structural unit derived from an alicyclic dihydroxy compound. By using an alicyclic dihydroxy compound, the heat resistance, solvent resistance, impact resistance, etc. tend to be improved. Specific examples of alicyclic dihydroxy compounds include tetramethylcyclobutanediol, cyclohexanedimethanol (CHDM), tricyclodecane dimethanol, adamantanediol, and pentacyclopentadecanedimethanol. Among these, tetramethylcyclobutanediol and cyclohexanedimethanol are preferred. Cyclohexanedimethanol includes 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol, and 1,4-cyclohexanedimethanol is preferred because it is easily available industrially. In addition, 2,2,4,4-tetramethyl-1,3-cyclobutanediol is generally used as tetramethylcyclobutanediol. The alicyclic dihydroxy compound may be used alone or in combination of two or more. As the alicyclic dihydroxy compound, it is preferable to use at least cyclohexanedimethanol, and more preferable to use tetramethylcyclobutanediol and cyclohexanedimethanol in combination.

[0021] The polyester resin (A) is preferably a copolymer polyester resin using two or more dihydroxy compounds as copolymerization components. Specifically, it is preferable to use a chain dihydroxy compound and an alicyclic dihydroxy compound as the dihydroxy compound used to obtain the polyester resin (A). Therefore, it is preferable that the polyester resin (A) has a structural unit derived from the chain dihydroxy compound and a structural unit derived from the alicyclic dihydroxy compound.

[0022] In the polyester resin (A), the ratio of the structural units derived from the alicyclic dihydroxy compound is preferably more than 65 mol% out of the total 100 mol% of the structural units derived from the chain dihydroxy compound and the structural units derived from the alicyclic dihydroxy compound. When the ratio of the structural units derived from the alicyclic dihydroxy compound exceeds 65 mol%, the heat resistance is excellent and the storage modulus of the resin composition in a high temperature environment is high. Therefore, the value of the thermal expansion rate of the film formed from the resin composition of the present invention is likely to be low. Furthermore, the impact resistance is likely to be good and the reliability in long-term use is likely to be improved. The above proportion of structural units derived from an alicyclic dihydroxy compound is more preferably 70 mol % or more, even more preferably 80 mol % or more, and even more preferably 90 mol % or more. In addition, from the viewpoint of improving low-temperature fusion properties by incorporating a certain amount or more of a chain dihydroxy compound, the above-mentioned proportion of structural units derived from an alicyclic dihydroxy compound is preferably 99 mol% or less, more preferably 98 mol% or less, and even more preferably 95 mol% or less.

[0023] As the dihydroxy compound used in the polyester resin (A), a dihydroxy compound other than a chain dihydroxy compound and an alicyclic dihydroxy compound (also referred to as "other dihydroxy compound") may be used within a range that does not impair the effects of the present invention. In the polyester resin (A), the content of the structural unit derived from the other dihydroxy compound is, for example, 20 mol% or less, preferably 10 mol% or less, more preferably 5 mol% or less, and most preferably 0 mol% in 100 mol of the structural unit derived from the dihydroxy compound in the polyester resin (A). Other dihydroxy compounds include p-xylenediol, 2,2-bis(4-hydroxyphenyl)propane (bisphenol A), tetrabromobisphenol A, tetrabromobisphenol A-bis(2-hydroxyethyl ether), α,α'-bis(4-hydroxyphenyl)-m-diisopropylbenzene (bisphenol M), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane, 4,4'-dihydroxy-3,3'-dimethyldiphenyl sulfide, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3,3-hexafluoropropane (bisphenol AF), and 1,1-bis(4-hydroxyphenyl)decane.

[0024] Of the above, from the viewpoints of low-temperature fusion property, heat resistance, and solvent resistance, the polyester resin (A) preferably contains a structural unit derived from ethylene glycol and a structural unit derived from cyclohexanedimethanol, and particularly preferably contains a structural unit derived from ethylene glycol, a structural unit derived from cyclohexanedimethanol, and a structural unit derived from tetramethylcyclobutanediol.

[0025] In the polyester resin (A), the content of structural units derived from ethylene glycol is preferably 1 mol % or more, more preferably 2 mol % or more, and even more preferably 5 mol % or more, based on 100 mol % of structural units derived from a dihydroxy compound, and is preferably 30 mol % or less, more preferably 20 mol % or less, and even more preferably 10 mol % or less. In addition, the content of structural units derived from cyclohexanedimethanol is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more, and is preferably 90 mol% or less, more preferably 85 mol% or less, and even more preferably 80 mol% or less, based on 100 mol% of structural units derived from a dihydroxy compound. Furthermore, the content of the structural unit derived from tetramethylcyclobutanediol is preferably less than the content of the structural unit derived from cyclohexanedimethanol. The content of the structural unit derived from tetramethylcyclobutanediol is preferably 4 mol% or more, more preferably 8 mol% or more, even more preferably 13 mol% or more, particularly preferably 15 mol% or more, and is preferably 49 mol% or less, more preferably 38 mol% or less, even more preferably 30 mol% or less, particularly preferably 25 mol% or less, based on 100 mol% of the structural units derived from the dihydroxy compound.

[0026] (glass transition temperature) The glass transition temperature (Tg) of the polyester resin (A) is 90°C or higher as described above. If the glass transition temperature is less than 90°C, the heat resistance becomes insufficient, the thermal expansion rate becomes high, the dimensional stability decreases, and the dimensional change during the production of a card or passport becomes large. This may result in a decrease in workability during the production of a card or passport, or the card or passport may be warped. Furthermore, even if an impact resistance improver is contained, the impact resistance may not be sufficiently improved, and the long-term reliability may not be sufficiently improved. From the viewpoints of heat resistance, impact resistance, etc., the glass transition temperature (Tg) of the polyester resin (A) is preferably 93° C. or higher, more preferably 95° C. or higher, even more preferably 98° C. or higher, and even more preferably 100° C. or higher. The glass transition temperature (Tg) of the polyester resin (A) is preferably higher from the viewpoint of heat resistance, but is preferably lower from the viewpoint of low-temperature fusion property, and is preferably 130° C. or lower, more preferably 120° C. or lower, and even more preferably 115° C. or lower. The glass transition temperature can be obtained by measuring the temperature dispersion of dynamic viscoelasticity of polyester resin (A) using a viscoelasticity spectrometer in accordance with JIS K7244-4:1999 at a strain of 0.07%, a frequency of 1 Hz, a heating rate of 3°C / min, and a tensile mode, and determining the temperature at the peak top of the loss modulus.

[0027] The polyester resin (A) is preferably an amorphous polyester, which tends to improve adhesion to other members such as resin films. The amorphous polyester may be any polyester that is substantially amorphous. As the substantially amorphous polyester (including low crystallinity), polyesters that do not show a clear crystalline melting peak when heated by a differential scanning calorimeter (DSC), polyesters that have crystallinity but have a slow crystallization rate and do not become highly crystalline when molded by an extrusion film forming method, and polyesters that have crystallinity but have a low crystalline melting heat (ΔHm) of 10 J / g or less when heated by a differential scanning calorimeter (DSC) can be used. In other words, the amorphous polyester in the present invention also includes "crystalline polyesters in an amorphous state". The polyester resin (A) may be used alone or in combination of two or more kinds.

[0028] [Impact resistance improver] The resin composition of the present invention contains an impact modifier. Resin compositions using polyester resins may lack long-term reliability in practical use, but by blending an impact modifier, the effects of external impacts such as bending and impacts in practical use are mitigated, resulting in good reliability in long-term use. The impact resistance improver may be a soft styrene-based resin, an elastomer, etc. The elastomer may be a core-shell type elastomer. The impact resistance improver may be used alone or in combination of two or more kinds. Among the above, the core-shell type elastomer is preferred as the impact resistance improver. By using the core-shell type elastomer, the impact resistance is further improved, and the reliability in long-term use is further improved.

[0029] Examples of the soft styrene-based resin include a block copolymer containing a styrene polymer block and a conjugated diene polymer block, and a block copolymer containing a styrene polymer block and an acrylonitrile block. The styrene content in the soft styrene-based resin is, for example, 5% by mass or more and 80% by mass or less, preferably 10% by mass or more and 50% by mass or less, and more preferably 15% by mass or more and 30% by mass or less. By having the styrene content in the above range, the effect of imparting impact resistance is further improved.

[0030] As the conjugated diene polymer block used in the soft styrene-based resin, a homopolymer of butadiene, isoprene, 1,3-pentadiene, or the like, a copolymer thereof, or a copolymer containing a monomer copolymerizable with the conjugated diene monomer in the block, or the like can be used. Specific examples of soft styrene resins include styrene-butadiene-styrene block copolymers (SBS), styrene-isoprene-styrene block copolymers (SIS), silicone-acrylic composite rubber-acrylonitrile-styrene copolymers (SAS), methyl methacrylate-maleic anhydride-styrene copolymers (SMM), acrylonitrile-styrene copolymers (AS), acrylonitrile-butadiene-styrene copolymers (ABS), acrylonitrile-styrene-acrylic rubber copolymers (ASA), acrylonitrile-ethylene propylene rubber-styrene copolymers (AES), etc. Specific examples of products include the "Kraton D" series manufactured by Kraton Polymers, the "AR-100" series manufactured by Aronkasei, the "Dialac" series manufactured by UMG ABS, and the "Delpet" series manufactured by Asahi Kasei Chemicals. As the soft styrene-based resin, the styrene-based elastomer described below, such as the "Dynaron" series manufactured by JSR Corporation, the "Tuftech" series manufactured by Asahi Kasei Chemicals Corporation, and the "Hybler" series manufactured by Kuraray Co., Ltd. can also be used.

[0031] Block copolymers include pure blocks, random blocks, tapered blocks, etc., and there is no particular restriction on the form of copolymerization. The block units may also have multiple repeating units. Specifically, in the case of styrene-butadiene block copolymers, the block units may be repeated multiple times, such as styrene-butadiene copolymers, styrene-butadiene-styrene block copolymers, and styrene-butadiene-styrene-butadiene block copolymers.

[0032] Hydrogenated styrene-butadiene-styrene block copolymers (SEBS) and hydrogenated styrene-isoprene-styrene block copolymers (SEPS), in which some or all of the double bonds in the conjugated diene polymer blocks of SBS and SIS are hydrogenated, can also be used. Specific examples of such products include the "Tuftech H" series manufactured by Asahi Kasei Chemicals Corporation and the "Kraton G" series manufactured by Kraton Polymers.

[0033] A functional group having polarity can be added to the soft styrene-based resin. Specific examples of the functional group having polarity include an acid anhydride group, a carboxylic acid group, a carboxylic acid ester group, a carboxylic acid chloride group, a carboxylic acid amide group, a carboxylate group, a sulfonic acid group, a sulfonic acid ester group, a sulfonic acid chloride group, a sulfonic acid amide group, a sulfonate group, an epoxy group, an amino group, an imide group, and an oxazoline group. Among these, it is preferable to add an acid anhydride group or an epoxy group. As the soft styrene-based resin to which a polar functional group is added, modified products of SEBS and SEPS are preferably used. Specific examples include maleic anhydride-modified SEBS, maleic anhydride-modified SEPS, epoxy-modified SEBS, and epoxy-modified SEPS. Specific commercial products include the "Tuftec M" series manufactured by Asahi Kasei Chemicals Corporation, the "Dynaron" series manufactured by JSR Corporation, and the "Epofriend" series manufactured by Daicel Chemical Industries, Ltd.

[0034] The soft styrene-based resin may be a styrene-based elastomer containing an elastomer component. Specifically, among the above, there may be mentioned block copolymers of a styrene component and butadiene, isoprene, 1,3-pentadiene, etc., and modified products or hydrogenated products thereof may also be used. More specifically, there may be mentioned SBS, SIS, SEBS, SEPS, etc.

[0035] The elastomer may be other than the styrene-based elastomer, and examples thereof include known elastomers such as polyester-based elastomers, polyolefin-based elastomers, diene-based elastomers, acrylic-based elastomers, polyamide-based elastomers, polyurethane-based elastomers, fluorine-based elastomers, and silicone-based elastomers. The elastomer is generally a thermoplastic elastomer. The elastomer is preferably a polyester-based elastomer or the above-mentioned styrene-based elastomer.

[0036] The polyester elastomer is a thermoplastic polyester having rubber properties at room temperature, preferably a thermoplastic elastomer mainly composed of a polyester block copolymer, and is preferably a block copolymer having a high melting point and high crystallinity aromatic polyester as a hard segment and an amorphous polyester or amorphous polyether as a soft segment. The content of the soft segment of the polyester elastomer is at least 20 to 95 mol% of the total segments, and in the case of a block copolymer of polybutylene terephthalate and polytetramethylene glycol (PTMG-PBT copolymer), it is 50 to 95 mol%. The preferred content of the soft segment is 50 to 90 mol%, particularly 60 to 85 mol%. Among them, polyester ether block copolymers, particularly PTMG-PBT copolymers, are preferred because they reduce the drop in transmittance.

[0037] The core-shell elastomer is composed of an innermost layer (i.e., a core) and one or more outer layers (i.e., shells) covering the innermost layer. The core-shell elastomer is preferably a core-shell graft copolymer in which a monomer component capable of being graft-copolymerized with the core is graft-copolymerized as the shell.

[0038] The core-shell type graft copolymer has a polymer component called a rubber component as the core. In the core-shell type graft copolymer, it is preferable that the polymer component constituting the core and a monomer component copolymerizable with this polymer component are graft-copolymerized as the shell. The core-shell graft copolymer may be produced by any of the following methods: bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. The copolymerization method may be either one-stage grafting or multi-stage grafting. However, commercially available core-shell elastomers can usually be used as they are. Examples of commercially available core-shell elastomers are given later.

[0039] Specific examples of the polymer component forming the core include butadiene-based rubbers such as polybutadiene and styrene-butadiene copolymers, isoprene-based rubbers, acrylic rubbers such as polybutyl acrylate, poly(2-ethylhexyl acrylate), and butyl acrylate-2-ethylhexyl acrylate copolymers, silicone-based rubbers such as polyorganosiloxane rubber, butadiene-acrylic composite rubbers, and silicone-acrylic composite rubbers such as IPN (Interpenetrating Polymer Network)-type composite rubbers consisting of polyorganosiloxane rubber and polyalkyl acrylate rubber, ethylene-α-olefin-based rubbers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers, ethylene-acrylic rubbers, and fluororubbers. These may be used alone or in combination of two or more. Among these, from the viewpoints of mechanical properties and surface appearance, at least one selected from butadiene-based rubber, acrylic-based rubber, silicone-based rubber, and silicone-acrylic composite rubber is preferred, and among these, at least one selected from butadiene-based rubber and silicone-acrylic composite rubber is more preferred.

[0040] Specific examples of the monomer component constituting the shell and capable of graft copolymerization with the polymer component of the core include aromatic vinyl compounds; vinyl cyanide compounds; (meth)acrylic compounds such as (meth)acrylic acid ester compounds, (meth)acrylic acid compounds, and epoxy group-containing (meth)acrylic acid ester compounds such as glycidyl (meth)acrylate; maleimide compounds such as maleimide, N-methylmaleimide, and N-phenylmaleimide; α,β-unsaturated carboxylic acid compounds such as maleic acid, phthalic acid, and itaconic acid, and their anhydrides (e.g., maleic anhydride, etc.). These monomer components may be used alone or in combination of two or more. Among these, aromatic vinyl compounds, vinyl cyanide compounds, and (meth)acrylic compounds are preferred from the standpoint of mechanical properties and surface appearance, and more preferably aromatic vinyl compounds and (meth)acrylic compounds, and especially (meth)acrylic acid ester compounds. Specific examples of aromatic vinyl compounds include styrene, α-methylstyrene, 1-vinylnaphthalene, 4-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, and halogenated styrenes. Of these, styrene and α-methylstyrene are more preferred. Specific examples of the (meth)acrylic acid ester compound include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, and octyl (meth)acrylate, and among these, methyl (meth)acrylate and ethyl (meth)acrylate, which are relatively easily available, are preferred, and methyl (meth)acrylate is more preferred. Note that "(meth)acrylic" is a general term for "acrylic" and "methacrylic".

[0041] As the core-shell type elastomer, a core-shell type graft copolymer is particularly preferred, which is composed of a core made of at least one polymer component selected from butadiene rubber, acrylic rubber, silicone rubber, and silicone-acrylic composite rubber, and a shell formed by graft copolymerizing a (meth)acrylic compound such as a (meth)acrylic acid ester or an aromatic vinyl compound around the core. The content of the polymer component in the core in the core-shell type graft copolymer is preferably 40% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. The total content of the (meth)acrylic compound (particularly, the (meth)acrylic acid ester) component and the aromatic vinyl compound component in the shell of the core-shell type graft copolymer is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, and even more preferably 70% by mass or more. In the shell, either the (meth)acrylic compound or the aromatic vinyl compound may be used alone, or these may be used in combination.

[0042] Preferred specific examples of the core-shell type elastomer include methyl methacrylate-butadiene-styrene copolymer (MBS), methyl methacrylate-acrylonitrile-butadiene-styrene copolymer (MABS), methyl methacrylate-butadiene copolymer (MB), methyl methacrylate-acrylic rubber copolymer (MA), methyl methacrylate-acrylic rubber-styrene copolymer (MAS), methyl methacrylate-acrylic-butadiene rubber copolymer, methyl methacrylate-acrylic-butadiene rubber-styrene copolymer, methyl methacrylate-(acrylic-silicone composite rubber) copolymer, and the like.

[0043] Commercially available core-shell type graft copolymers include, for example, "Paraloid EXL2602", "Paraloid EXL2603", "Paraloid EXL2690", "Paraloid EXL2691J", "Paraloid EXL2650J", "Paraloid EXL2655", "Paraloid EXL2311", "Paraloid EXL2313", "Paraloid EXL2315", "Paraloid KM330", "Paraloid KM336P", and "Paraloid Examples of such polymers include "KCZ201", "Metabrene C-223A", "Metabrene E-901", "Metabrene S-2001", "Metabrene W-450A", and "Metabrene SRK-200" manufactured by Mitsubishi Chemical Corporation, and "Kane Ace M-210", "Kane Ace M-511", "Kane Ace M-600", "Kane Ace M-400", "Kane Ace M-580", "Kane Ace M-590", "Kane Ace M-711", "Kane Ace MR-01", and "Kane Ace M-300" manufactured by Kaneka Corporation. These impact resistance improvers such as core-shell type graft copolymers may be used alone or in combination of two or more kinds.

[0044] In the resin composition, the content of the impact resistance improver is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the resin component. When the content of the impact resistance improver is 1 part by mass or more, the influence caused by external impact is moderately alleviated, and long-term reliability is improved. When the content is 40 parts by mass or less, an effect commensurate with the content can be exhibited, and various physical properties such as heat resistance of the film formed from the resin composition can also be prevented from being deteriorated. From these viewpoints, the content of the impact modifier in the resin composition is more preferably 2.5 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 7 parts by mass or more, based on 100 parts by mass of the resin component, and is more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, even more preferably 16 parts by mass or less, and particularly preferably 12 parts by mass or less.

[0045] [Polyester resin (B)] The resin composition of the present invention may contain a polyester resin (B) other than the above-mentioned polyester resin (A) as a resin component. The polyester resin (B) is a polyester obtained by polycondensation of a dicarboxylic acid and a dihydroxy compound. As the dicarboxylic acid, a dicarboxylic acid derivative such as an ester or an acid halide of a dicarboxylic acid may be used for synthesizing the polyester resin (B). By containing the polyester resin (B) in addition to the polyester resin (A), the resin composition is likely to have various properties, for example, low-temperature fusion properties are likely to be improved. In addition, the printability tends to be improved.

[0046] In the polyester resin (B), it is preferable to use an aromatic dicarboxylic acid as the dicarboxylic acid from the viewpoint of heat resistance, and therefore, it is preferable that the polyester resin (B) contains a structural unit derived from an aromatic dicarboxylic acid. Specific examples of the aromatic dicarboxylic acid are as described in the polyester resin (A), and the same applies to suitable compounds. The aromatic dicarboxylic acid may be used alone or in combination of two or more kinds. In the polyester resin (B), the structural units derived from aromatic dicarboxylic acids are preferably contained in the structures derived from dicarboxylic acids in the polyester resin (A) at 80 mol % or more, more preferably at 90 mol % or more, and preferably at most 100 mol %, and most preferably at 100 mol %. The polyester resin (B) may contain a small amount (usually in the range of 20 mol % or less) of structural units derived from an aliphatic dicarboxylic acid. Specific examples of the aliphatic dicarboxylic acid are as described above for the polyester resin (B).

[0047] The polyester resin (B) is preferably a copolymer polyester resin using two or more dihydroxy compounds as copolymerization components. The polyester resin (B) may use at least one of a chain dihydroxy compound and an alicyclic dihydroxy compound as the dihydroxy compound, but it is preferable to use both of them. Therefore, the polyester resin (B) preferably contains a structural unit derived from a chain dihydroxy compound and a structural unit derived from an alicyclic dihydroxy compound. Specific examples of the chain dihydroxy compound used in the polyester resin (B) are as described for the polyester resin (A), but are preferably one or more selected from ethylene glycol, diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol. Specific examples of the alicyclic dihydroxy compound used in the polyester resin (B) are as described in the polyester resin (A), but are preferably one or more selected from tetramethylcyclobutanediol and cyclohexanedimethanol, more preferably cyclohexanedimethanol. As for the cyclohexanedimethanol, 1,4-cyclohexanedimethanol is preferred as described above.

[0048] In the polyester resin (B), the proportion of structural units derived from alicyclic dihydroxy compounds is preferably 65 mol % or less, more preferably 50 mol % or less, and more preferably 40 mol % or less, out of the total of 100 mol % of structural units derived from chain dihydroxy compounds and structural units derived from alicyclic dihydroxy compounds. When the proportion of structural units derived from alicyclic dihydroxy compounds is reduced as described above, the content of structural units derived from chain dihydroxy compounds in the polyester resin (B) increases, and the low-temperature fusion properties of the resin composition are easily improved. In addition, from the viewpoint of improving heat resistance by incorporating a certain amount or more of an alicyclic dihydroxy compound, the above-mentioned proportion of structural units derived from an alicyclic dihydroxy compound is preferably 5 mol % or more, more preferably 15 mol % or more, and even more preferably 20 mol % or more.

[0049] The glass transition temperature (Tg) of the polyester resin (B) is preferably less than 90° C., but is preferably 88° C. or less, more preferably 85° C. or less, and even more preferably 82° C. or less. From the viewpoint of improving the heat resistance and impact resistance of the resin composition, the glass transition temperature (Tg) of the polyester resin (B) is preferably 70° C. or more, more preferably 73° C. or more, and even more preferably 75° C. or more. The method for measuring the glass transition temperature (Tg) is as described above. The polyester resin (B) is preferably an amorphous polyester, which tends to improve adhesion to other members such as resin films.

[0050] (Content of polyester resins (A) and (B)) The content of polyester resin (A) in the resin composition is preferably more than 50 parts by mass per 100 parts by mass of the total amount of polyester resin (A) and polyester resin (B). When the content of polyester resin (A) is more than 50 parts by mass, the low-temperature fusion property is improved while heat resistance is well maintained, and dimensional change during heat processing is unlikely to occur. Therefore, the workability during the production of cards or passports is improved, and warping of the obtained cards or passports can be prevented. Furthermore, impact resistance is likely to be good, and reliability during long-term use is likely to be improved. In addition, solvent resistance is likely to be good. The content of the polyester resin (A) in the resin composition is more preferably 60 parts by mass or more, and even more preferably 70 parts by mass or more, per 100 parts by mass of the total amount of the polyester resin (A) and the polyester resin (B). Furthermore, the resin composition of the present invention may not contain the polyester resin (B) as described above. Therefore, the content of the polyester resin (A) in the resin composition may be 100 parts by mass or less per 100 parts by mass of the total amount of the polyester resin (A) and the polyester resin (B). However, in order to easily exert the effect of including the polyester resin (B) when the polyester resin (B) is included in the resin composition, the content of the polyester resin (B) is preferably a certain amount or more. Therefore, the content of the polyester resin (A) is preferably 95 parts by mass or less, more preferably 90 parts by mass or less, and even more preferably 85 parts by mass or less, relative to 100 parts by mass of the total amount of the polyester resin (A) and the polyester resin (B).

[0051] (Other Ingredients) As described below, the resin composition may be used as a core sheet for a card or passport, a sheet for laser marking, or a protective sheet, and additives may be added as appropriate depending on the sheet to be used.

[0052] When the resin composition is used for a core sheet, for example, it is preferable that the resin composition contains a colorant. Examples of the colorant include titanium oxide, barium oxide, and zinc oxide as white pigments, iron oxide and titanium yellow as yellow pigments, iron oxide as red pigments, and cobalt blue ultramarine as blue pigments. Dyes such as white dyes may also be used. However, in order to enhance contrast, light-colored and pale colors are preferred. Among the above-mentioned colorants, white dyes and white pigments, which have outstanding contrast, are more preferred.

[0053] In addition, for example, the resin composition used in the laser marking sheet may contain a laser coloring agent. The laser coloring agent is not particularly limited as long as it has the function of generating heat by irradiation with a laser beam, and may be a so-called self-coloring type coloring agent that generates color by itself by irradiation with a laser beam, or may not generate color by itself. When the laser coloring agent generates heat, at least the surrounding forming material is carbonized, and the desired print appears on the laser marking sheet. Furthermore, when a self-coloring laser coloring agent is used, the coloring of the laser coloring agent and the coloring of the carbonized material generated by carbonizing the forming material of the laminate are synergistically combined to produce a print that is dark in color and has excellent visibility. When the laser coloring agent generates color, the color is not particularly limited, but from the viewpoint of visibility, it is preferable to use a laser coloring agent that can generate dark colors including black, navy blue, and brown.

[0054] The laser coloring agent may be a metal oxide or a compound other than a metal oxide. The metal oxide is not limited as long as it has a laser coloring effect, and examples of the metal oxide include iron oxide, copper oxide, zinc oxide, tin oxide, cobalt oxide, nickel oxide, bismuth oxide, indium oxide, antimony oxide, tungsten oxide, neodymium oxide, mica, hydrotalcite, montmorillonite, and smectite. Laser coloring agents other than metal oxides may also be used, including metals such as iron, copper, zinc, tin, gold, silver, cobalt, nickel, bismuth, antimony, and aluminum, and metal salts thereof such as iron chloride, iron nitrate, iron phosphate, copper chloride, copper nitrate, copper phosphate, zinc chloride, zinc nitrate, zinc phosphate, nickel chloride, nickel nitrate, bismuth subcarbonate, and bismuth nitrate, metal hydroxides such as magnesium hydroxide, lanthanum hydroxide, nickel hydroxide, and bismuth hydroxide, and metal borides such as zirconium boride, titanium boride, and lanthanum boride. Among the metal borides, hexaborides have near-infrared absorption ability, and among them, lanthanum hexaboride is preferred because it has excellent laser light absorption efficiency. In addition, dye systems represented by leuco dyes such as fluoran, phenothiazine, spiropyran, triphenylmethaphthalide, and rhodamine lactam, and carbon black can also be used. As the laser coloring agent, it is preferable to use a bismuth-based metal oxide such as bismuth oxide or a metal oxide containing bismuth and at least one metal selected from Zn, Ti, Al, Zr, Sr, Nd, and Nb. The laser color developing agent may be used alone or in combination of two or more kinds.

[0055] The resin composition may also contain a lubricant. By containing a lubricant, the surface resistivity of the film made of the resin composition is reduced, suppressing charging, and the surface slipperiness of the film is improved, so that the film is less likely to adhere to another film or press plate and become difficult to peel off. In addition, when the surface resistivity is low, static electricity is less likely to be generated when the film is unwound from the roll, and it is easy to prevent sparks from being generated during unwounding and scratching the surface of the film, etc., and further, due to the improvement in slipperiness and the decrease in surface resistivity, it is easy to prevent the film from meandering or slanting when unwound from the roll and unwound from causing misalignment, twisting, wrinkles, etc., when the film is unwound from the roll and unwound. Therefore, the handling and processability are improved. Furthermore, when the surface resistivity is low, floating dust is attracted by static electricity and adheres to the surface of the film, etc., and problems such as foreign matter being mixed into the obtained laminated film or card are less likely to occur, and the dustproofness is further improved. In addition, since the slipperiness is good, the film surface is less likely to be scratched even when rubbed, and tends to have excellent scratch resistance. Furthermore, it is presumed that the improved wettability due to the lubricant improves printability when printing on a film made of a resin composition. The printability means the compatibility of the ink with the film when printing on the film made of a resin composition. When the printability is improved, there is a tendency for the ink to be printed neatly on the film without repelling or the like.

[0056] Lubricants generally include compounds having polar moieties such as acids, esters, hydroxyl groups, amide groups, and metal salts in the molecule, and non-polar moieties such as aliphatic groups. In addition, compounds other than these compounds that improve the sliding properties with other materials such as metals and resins can be used as lubricants. The surface resistivity can be reduced by using a lubricant having a polar moiety. In addition, the sticking to the press plate can be suppressed by using a lubricant having a non-polar moiety. Specific examples of the lubricant include polyalkylene glycol, fatty acid ester, metal salt having an aliphatic group, fluorine-based polymer, fatty acid amide, aliphatic alcohol, fatty acid, and aliphatic hydrocarbon compound. By adding these lubricants to the polyester resin (A), the above-mentioned various properties are easily exhibited. Among these, the lubricant is preferably at least one selected from polyalkylene glycol, fatty acid ester, metal salt having an aliphatic group, and fluorine-based polymer.

[0057] (Polyalkylene glycol) The polyalkylene glycol may be polyethylene glycol, polypropylene glycol, polybutylene glycol, polytetramethylene glycol, or a copolymer of ethylene oxide and propylene oxide. The polyalkylene glycol may have a branch in the molecular skeleton. Among these, polyethylene glycol is preferred. The polyalkylene glycol is preferably a solid wax that is solid at room temperature (23°C). A solid wax is preferable because it is easily mixed with pellets and is less likely to volatilize due to the heat required for processing into a sheet. The polyalkylene glycol that becomes the solid wax has a number average molecular weight of, for example, 500 to 5000. The number average molecular weight refers to the number average molecule calculated based on the hydroxyl value measured in accordance with JIS K1577. The polyalkylene glycol may be used alone or in combination of two or more kinds.

[0058] (Fatty acid ester) The fatty acid ester may be a known fatty acid ester used as a lubricant. The fatty acid ester is an ester made from fatty acids and various alcohols, and preferably has a long-chain aliphatic group and an ester group in the molecule. Specific examples of fatty acid ester lubricants include higher fatty acid esters of monohydric alcohols, higher fatty acid esters or partial esters of polyhydric alcohols, or partially saponified products thereof, etc. The higher fatty acids used in the higher fatty acid esters have, for example, 10 or more carbon atoms, preferably 12 or more carbon atoms, more preferably 16 or more carbon atoms, and even more preferably 20 or more carbon atoms, and preferably 36 or less carbon atoms, more preferably 32 or less carbon atoms. Specifically, examples of such fatty acids include montanic acid esters, partially saponified montanic acid esters, methyl laurate, methyl myristate, methyl palmitate, methyl stearate, methyl oleate, methyl erucate, methyl behenate, butyl laurate, butyl stearate, isopropyl myristate, isopropyl palmitate, octyl palmitate, coconut fatty acid octyl esters, octyl stearate, cow fatty acid octyl esters, lauryl laurate, stearyl stearate, behenyl behenate, cetyl myristate, neopentyl polyol fatty acid esters such as neopentyl glycol dioleate and neopentyl glycol dicaprate, and trimeyl polyol fatty acid esters such as trimethylolpropane trioleate. Examples of such fatty acid esters include various trimethylolpropane fatty acid esters such as trimethylolpropane trifatty acid esters and trimethylolpropane difatty acid esters such as trimethylolpropane dicaprate, pentaerythritol fatty acid esters such as pentaerythritol tetraoleate, dipentaerythritol fatty acid esters such as dipentaerythritol hexaisononanoate, fatty acid glycerides such as stearate monoglyceride, stearate diglyceride, stearate triglyceride, oleate monoglyceride, oleate diglyceride, oleate triglyceride, pentaerythritol fatty acid condensation esters, and trimethylolpropane fatty acid condensation esters. Among these, montanic acid esters are preferred. The fatty acid esters may be used alone or in combination of two or more.

[0059] (Metal salts having an aliphatic group) The metal salt used as the lubricant may be a metal salt having an aliphatic group. By using a metal salt having an aliphatic group, it becomes easier to reduce the surface resistivity and to exhibit various effects. Examples of the aliphatic group include an aliphatic hydrocarbon group and an aliphatic acyl group. The aliphatic group is not particularly limited, but preferably has 8 or more carbon atoms, more preferably has 10 or more carbon atoms, and preferably has 30 or less carbon atoms, more preferably has 24 or less carbon atoms, and even more preferably has 16 or less carbon atoms. Specific examples of the metal salt include metal salts of fatty acids and metal salts of alkylbenzenesulfonic acids, with metal salts of alkylbenzenesulfonic acids being preferred.

[0060] The fatty acid metal salts are salts of fatty acids, for example, higher fatty acids having about 8 to 30 carbon atoms, preferably 10 to 24 carbon atoms, such as stearic acid, lauric acid, myristic acid, and castor oil fatty acid, with metals such as aluminum, calcium, zinc, magnesium, lead, and barium, and preferred examples include calcium stearate, zinc stearate, and magnesium stearate. The metal alkylbenzenesulfonate may be one in which the number of carbon atoms in the alkyl group is preferably 8 to 24, more preferably 10 to 16. The metal used is preferably sodium, calcium, magnesium, potassium, etc., and particularly preferably sodium. A specific example of a suitable metal salt of alkylbenzenesulfonate is sodium dodecylbenzenesulfonate. The metal salts may be used alone or in combination of two or more kinds.

[0061] (Fluorine-based polymer) The fluorine-based polymer may be a fluorine resin having a carbon-fluorine bond in the molecule.Specific examples of the fluorine-based polymer include polytetrafluoroethylene, polytrifluoroethylene, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene-perfluoroalkylvinyl ether copolymer, a fluorine-based polymer having a fluoroalkyl group at both ends or one end of a polymer chain, a perfluorocarboxylic acid ester, etc. Among these, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, and the like are preferable. The fluorine-based polymers may be used alone or in combination of two or more kinds.

[0062] (Aliphatic amide) Examples of fatty acid amides include known fatty acid amides that can be used as lubricants. Fatty acid amides are amides consisting of fatty acids and amines, and have a long-chain aliphatic group and an amide group in the molecule, and are also called fatty acid amides. Specific examples include monoamides, substituted amides, bisamides, methylol amides, ethanol amides, ester amides, substituted ureas, and polycondensates of fatty acids and amines. The fatty acids used may be saturated or unsaturated. The number of carbon atoms of the fatty acid is, for example, about 8 to 30, and preferably 10 to 24. Preferred examples of fatty acid amides include stearic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, stearyl erucic acid amide, ethylene bis erucic acid amide, ethylene bis stearic acid amide, ethylene bis oleic acid amide, N-oleyl palmitamide, and ethylenediamine-stearic acid-sebacic acid polycondensates. The fatty acid amides may be used alone or in combination of two or more.

[0063] (Fatty alcohol) The fatty alcohol may be any known fatty alcohol that can be used as a lubricant. The fatty alcohol may be, for example, a fatty alcohol having 6 to 30 carbon atoms, preferably 10 to 24 carbon atoms. Specific examples of the fatty alcohol include caproyl alcohol, caprylyl alcohol, capryl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, arachidyl alcohol, and behenyl alcohol, and preferably stearyl alcohol. The fatty acid alcohols may be used alone or in combination of two or more.

[0064] (fatty acid) The fatty acid may be a known fatty acid that can be used as a lubricant. For example, the fatty acid may be a fatty acid having 6 to 30 carbon atoms, preferably 10 to 24 carbon atoms. Specific examples of the fatty acid include saturated fatty acids such as caproic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, and behenic acid, and unsaturated fatty acids such as oleic acid and erucic acid, and preferably stearic acid. The fatty acids may be used alone or in combination of two or more.

[0065] (Aliphatic hydrocarbon compounds) The aliphatic hydrocarbon compounds include known aliphatic hydrocarbon compounds that can be used as lubricants. Specific examples of the aliphatic hydrocarbon compounds include paraffin waxes such as liquid paraffin, microcrystalline wax, natural paraffin, and synthetic paraffin having 16 or more carbon atoms, polyolefin waxes such as polyethylene wax, and partial oxides, fluorides, and chlorides thereof. The aliphatic hydrocarbon compounds may be used alone or in combination of two or more kinds.

[0066] In the resin composition, the lubricant may be used alone or in combination of two or more. When using two or more in combination, for example, it is preferable to use polyalkylene glycol and a metal salt having an aliphatic group in combination, and among them, it is more preferable to use polyethylene glycol and a metal salt of alkylbenzenesulfonic acid in combination. By using these two types of lubricants in combination, the film made of the resin composition of the present invention is less likely to adhere to not only other resin films but also press plates, so that the handling and processability are more excellent. When a polyalkylene glycol is used in combination with a metal salt having an aliphatic group, the ratio of the polyalkylene glycol to the metal salt having an aliphatic group (polyalkylene glycol / metal salt), in terms of mass ratio, is preferably 1 / 9 or more and 9 / 1 or less, more preferably 1 / 5 or more and 5 / 1 or less, and even more preferably 1 / 3 or more and 3 / 1 or less.

[0067] It is also preferable to use fatty acid ester and fluoropolymer in combination. By using these two kinds of lubricants in combination, the film made of the resin composition of the present invention is less likely to adhere to not only the resin film but also the press plate, so that the handling and processability are more excellent. When fatty acid ester and fluoropolymer are used in combination, the ratio of fluoropolymer to fatty acid ester (fluoropolymer / fatty acid ester) is preferably 1 / 9 or more and 9 / 1 or less, more preferably 1 / 6 or more and 6 / 1 or less, even more preferably 1 / 4 or more and 4 / 1 or less, and even more preferably 1 / 3 or more and 3 / 1 or less, by mass ratio.

[0068] In addition, three or more kinds of lubricants may be used in combination, for example, four kinds of lubricants, namely, polyalkylene glycol, metal salt having an aliphatic group, fatty acid ester, and fluoropolymer, may be used in combination. When four kinds of lubricants are used in combination, the content ratio of polyalkylene glycol to metal salt, and the content ratio of fatty acid ester to fluoropolymer may be as described above.

[0069] The content of the lubricant in the resin composition is preferably 0.01 parts by mass or more and 5 parts by mass or less with respect to 100 parts by mass of the resin component contained in the resin composition. By being 0.01 parts by mass or more, the surface resistivity of the film formed from the resin composition is low, charging is prevented, and the slipperiness is good, and the processability, handling property, dust resistance, scratch resistance, etc. are likely to be improved. In addition, it is estimated that the wettability is appropriately increased and the printability is also likely to be improved. In addition, by making it 5 parts by mass or less, it is possible to exert an effect commensurate with the content, and it is also possible to suppress the deterioration of the physical properties of the film formed from the resin composition and the deterioration of the printability. From the above viewpoints, the content of the lubricant in the resin composition is more preferably 0.1 parts by mass or more, even more preferably 0.4 parts by mass or more, even more preferably 0.6 parts by mass or more, and particularly preferably 0.9 parts by mass or more, relative to 100 parts by mass of the resin component. Also, it is more preferably 3 parts by mass or less, even more preferably 2 parts by mass or less, and particularly preferably 1.5 parts by mass or less.

[0070] The resin composition may contain known additives used in resin materials other than those mentioned above, such as antioxidants, heat stabilizers, process stabilizers, ultraviolet absorbers, light stabilizers, matting agents, processing aids, metal deactivators, residual polymerization catalyst deactivators, antibacterial and antifungal agents, antiviral agents, antistatic agents, flame retardants, and fillers.

[0071] The resin composition of the present invention may use polyester resin (A) alone or polyester resin (A) and polyester resin (B) as the resin component, but may contain resins other than polyester resins (A) and (B) within the scope of the present invention. As such a resin component, a known resin that is used for general purposes may be used, but it is preferable to use a resin that is compatible with polyester resin (A) or polyester resins (A and (B). In this specification, the resin component does not include those used as the impact resistance improver described above. The resin components constituting the resin composition may contain polyester resin (A) or polyester resin (A) and polyester resin (B) as main components, and the total content of polyester resins (A) and (B) is preferably 70 mass% or more, more preferably 90 mass% or more, and most preferably 100 mass% based on the total amount of resin components contained in the resin composition.

[0072] (Storage modulus) The resin composition of the present invention has a storage modulus of 3×10 at 90° C. 7 The storage modulus at 90° C. is preferably 3×10 Pa or more. 7 When the storage modulus is 1×10 Pa or more, deformation is unlikely to occur when heated, and workability is good when producing cards or passports. Also, cards and passports are unlikely to warp. In addition, durability that can withstand long-term use is likely to be obtained. The storage modulus of the resin composition at 90° C. is 1×10 8 Pa or more is preferable, 3×10 8 Pa or more is more preferable, and 5×10 8 It is even more preferable that the tensile strength is 1 Pa or more. The upper limit of the storage modulus is not particularly limited, but is, for example, 5×10 10 Pa or less, preferably 1×10 10 Pa or less.

[0073] The storage modulus is the value of the tensile storage modulus obtained by dynamic viscoelasticity measurement according to JIS K7244-4:1999, and is described in detail in the Examples. The test piece for obtaining the tensile storage modulus may be prepared by, for example, press molding, extrusion molding, or the like, from the resin composition to form a film, and the film may be used as the test piece. In the case of extrusion molding, it is preferable to prepare the film without stretching, but if there is directionality, it is preferable to measure in MD. In the case of no directionality such as press molding, only one direction is measured, and the measured value is taken as the storage modulus. The MD (Machine Direction) is the flow direction of the resin, and the TD (Transverse Direction) is the direction perpendicular to the MD along the surface direction of the film.

[0074] (Recycled raw material) The resin composition of the present invention may contain recycled raw materials. The use of recycled raw materials can contribute to global environmental protection, such as reducing waste and energy consumption. The recycled raw materials may be raw materials that have been regenerated from recovered products, waste, etc. by a chemical regeneration method involving chemical reactions. In addition, the recycled raw materials may be raw materials that have been regenerated from recovered products, waste, etc. by a physical regeneration method (mechanical recycling). As the recycled raw materials, it is preferable to use recycled raw materials for at least a part of the polyester resin (A) and polyester resin (B), and it is more preferable to use recycled raw materials for at least a part of the polyester resin (A). Note that the polyester resin (A) and polyester resin (B) composed of recycled raw materials are also called recycled polyester resin (A) and recycled polyester resin (B), respectively.

[0075] The content of the recycled polyester resin (A) and the recycled polyester resin (B) in the resin composition is, for example, 30% by mass or more, preferably 50% by mass or more, and more preferably 70% by mass or more, based on the total amount of the polyester resin (A) and the polyester resin (B). From the viewpoint of protecting the global environment, the higher the content of the recycled raw materials, the better, and there is no particular restriction as long as it is 100% by mass or less.

[0076] The recycled polyester resin (A) or the recycled polyester resin (B) may be one that has been regenerated by a chemical regeneration method as described above. Specifically, the recycled polyester resin (A) or the recycled polyester resin (B) can be obtained by depolymerizing a discarded polyester resin, and repolymerizing the resulting intermediate or monomer to synthesize the polyester resin (A) or the polyester resin (B). In addition, the recycled polyester resin (A) or the recycled polyester resin (B) may be prepared by collecting polyester resin products or scraps generated during the production process, sorting and washing as necessary, and then processing such as melting and pulverization, followed by appropriate processing such as granulation, pulverization, pelletization, and flaking, so that the resin composition can be used as a raw material in the form of powder, granules, pellets, flakes, etc., and used as a recycled raw material. In addition, in the process of obtaining the recycled raw material, the molecular weight may be increased by solid-phase polymerization, etc. That is, the recycled polyester resin (A) or the recycled polyester resin (B) may be one that is regenerated by a physical regeneration method that does not involve a chemical reaction, or the molecular weight may be increased by a chemical change while being regenerated by a physical regeneration method.

[0077] The recycled polyester resin (A) or the recycled polyester resin (B) is preferably a recycled polyester resin recycled from scraps generated during the production process. Scraps generated during the production process have a relatively stable raw material composition, and the raw material composition is often known, so that they are easy to recycle as recycled raw materials. The scraps generated during the production process are generated during the process of processing the synthesized polyester resin into a specified product form (any product form such as film, sheet, fiber, strand, block, pellet, powder, or other molded product) and are not used as a product.

[0078] (Method of producing resin composition) The resin composition of the present invention may be obtained by mixing raw materials constituting the resin composition, such as the polyester resin (A), the impact resistance improver, the polyester resin (B) which is optionally blended, the lubricant, and other additives. In addition, when the resin composition contains recycled raw materials, the recycled raw materials may be blended into the resin composition and mixed with other raw materials to obtain the resin composition. The raw materials may be mixed by melt kneading while heating in an extruder, a plastomill or the like, but the raw materials constituting the resin composition may also be dry-blended in a tumbler or the like and used as is. The melt-kneading temperature is appropriately adjusted depending on the type and mixing ratio of the resin, and the presence and type of additives, but from the viewpoint of productivity, it is preferably 220° C. or higher, more preferably 230° C. or higher, and even more preferably 240° C. or higher. It is also preferably 300° C. or lower, more preferably 280° C. or lower, and even more preferably 270° C. or lower. If the melt-kneading temperature is within this range, it is easy to sufficiently flow the resin while suppressing decomposition and crosslinking.

[0079] <Card or passport film> The card or passport film of the present invention (hereinafter sometimes referred to as "the film") is a film made of the above-mentioned resin composition. The thickness of the film is not particularly limited and may be appropriately adjusted depending on the purpose of use, but is, for example, 5 μm or more, preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and is 1000 μm or less, preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 200 μm or less. The present film may be a single layer or may be one layer of a multi-layer laminate, in which only one layer may be composed of the present film, or two or more layers may be composed of the present film. As will be described later, cards or passports are generally constructed by stacking a number of resin layers, and it is preferable that the present film constitutes at least one of these layers.

[0080] (Heating expansion / contraction rate) The present film preferably has a thermal expansion / contraction rate of -1.3% or more when heated at 100° C. for 10 minutes, as expressed by the following formula. The thermal expansion / contraction rate may be calculated by marking a standard line on the measurement sample and measuring the distance between the standard lines before and after the heat treatment. Heat expansion rate (%) = [Standard line spacing after heat treatment - Standard line spacing before heat treatment] / Standard line spacing before heat treatment x 100

[0081] The heat expansion rate is a negative value when the film shrinks due to heating, and a positive value when the film expands due to heating. Generally, resin films shrink when heated, so the heat expansion rate of the present film is usually a negative value, but a lower absolute value indicates less shrinkage when heated. Therefore, if the heat expansion rate of the present film is set to -1.3% or more as described above, the dimensional change during the production of a card or passport becomes relatively small, and the deterioration of workability and the occurrence of warping can be reduced. From these viewpoints, the thermal expansion rate is more preferably -1% or more, even more preferably -0.7% or more, even more preferably -0.5% or more, even more preferably -0.4% or more, and particularly preferably -0.3% or more. On the other hand, as described above, the thermal expansion rate is preferably closer to 0%, and therefore the upper limit of the thermal expansion rate is generally 0%. The thermal expansion rate described above should be measured in two directions, one in the plane direction of the film and the other perpendicular to that direction, and the lower value (i.e., the value with the larger thermal shrinkage) should be used. However, if the MD and TD directions are known, it is advisable to measure the thermal expansion rate in both MD and TD.

[0082] (Method of manufacturing card or passport film) The card or passport film (the present film) can be produced by a known method, but it is preferable to obtain a resin composition for forming the present film as described above and form the resin composition into a film. The method for forming the resin composition into a film is not particularly limited, and may be press molding or extrusion molding, but extrusion molding is preferred from the standpoint of productivity and cost. When forming a multi-layer laminate using the present film, a plurality of resin films may be laminated by a known lamination method, or a resin composition for forming another resin layer may be melt-extruded onto a resin film, or a multi-layer structure may be formed by co-extrusion.

[0083] <Cards and passports> The card of the present invention comprises the above-mentioned present film, and the passport of the present invention comprises the above-mentioned present film. Examples of cards include IC cards, magnetic cards, driver's licenses, residence cards, qualification certificates, employee ID cards, student ID cards, My Number cards, seal registration certificates, vehicle inspection certificates, tag cards, prepaid cards, cash cards, credit cards, ETC cards, SIM cards, and B-CAS cards. The card or passport may include a core sheet. The card or passport may also include, in addition to the core sheet, one or both of a laser marking sheet and a protective sheet.

[0084] (card) A preferred layer structure of the card will be described in more detail below. The card is preferably laminated with laser marking sheets on both sides of the core sheet. Specifically, a card 20A consisting of laser marking sheet 1 / core sheet 2 / laser marking sheet 1 as shown in FIG. 1(a), or a card 20B consisting of protective sheet 4 / laser marking sheet 1 / core sheet 2 / laser marking sheet 1 / protective sheet 4 as shown in FIG. 1(b) is preferred. The laser marking sheet 1 may be omitted, and a card 20C consisting of protective sheet 4 / core sheet 2 / protective sheet 4 as shown in FIG. 1(c) may be used. In each of the cards 20A to 20C, the layer structures on both sides of the core sheet 2 are the same, but may be different on each side. For example, the laser marking sheet 1 and the protective sheet 4 may be provided in this order on one side of the core sheet 2, and only the protective sheet 4 may be provided on the other side of the core sheet 2.

[0085] The laser marking sheet 1 may be composed of a single resin layer, but is preferably a laminate of a multi-layer structure composed of multiple resin layers. The laser marking sheet 1 preferably includes a resin layer containing a laser coloring agent, and when composed of a single resin layer, it is preferable that one of the resin layers contains a laser coloring agent. In addition, when it is a multi-layer structure, it is preferable that one or more of the multiple resin layers contains a laser coloring agent.

[0086] The core sheet 2 is usually made of a single resin layer, but may be made of multiple resin layers. The thickness of the core sheet is, for example, about 400 to 700 μm. The core sheet is preferably a colored sheet containing an appropriate amount of colorant. Specific examples of the colorant used in the core sheet are as described above.

[0087] A dye-sublimation thermal transfer image receiving layer may be provided on the outermost surface of the laser marking sheet, or on the outermost surface of the core sheet when the laser marking sheet is omitted. In the laser marking sheet and the core sheet, the dye-sublimation thermal transfer image receiving layer is preferably provided on the front surface that is the visible side, and therefore the dye-sublimation thermal transfer image receiving layer provided on the laser marking sheet is preferably provided on the opposite side to the core sheet. The same applies to a passport, which will be described later.

[0088] The dye-sublimation thermal transfer image-receiving layer may be a conventionally known one, for example, made by adding various additives such as a release agent, a stabilizer, and an ultraviolet absorber, as necessary, to a varnish mainly composed of a resin that is easy to transfer or dye a coloring material. Resins that are easily dyeable and are used in the sublimation thermal transfer image receiving layer include polyolefin resins such as polypropylene, halogenated resins such as polyvinyl chloride and polyvinylidene chloride, vinyl resins such as polyvinyl acetate and polyacrylic esters, and copolymers thereof, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polystyrene resins, polyamide resins, copolymers of olefins such as ethylene and propylene with other vinyl monomers, ionomers, cellulose derivatives, etc., used alone or in mixtures, and among these, polyester resins and vinyl resins are preferred. The dye-sublimation type thermal transfer image receiving layer can be formed by dissolving and dispersing the above-mentioned resin in a solvent such as an organic solvent or water, and then coating the solution.

[0089] The protective sheet is laminated to protect the card. The protective sheet may be composed of a single resin layer, or may be a laminate having a multi-layer structure composed of a plurality of resin layers. The protective sheet is also called an oversheet, and generally constitutes the outermost layer of the card. When the protective sheet is laminated on the outside of the laser marking sheet 1, it suppresses so-called "blistering" that occurs when the laser-marked portion foams due to irradiation with laser light.

[0090] The card may be manufactured by stacking the core sheet, the laser marking sheet, and the protective sheet as appropriate so as to form the layer structure described above, pressing and heat fusing the sheets, and then performing a punching process, etc. Alternatively, the sheets may be bonded together using an appropriate adhesive, etc., instead of heat fusing.

[0091] (passport) Next, a preferred layer structure of the passport will be described in more detail. The film is preferably used for a so-called electronic passport equipped with an IC chip as a passport, and particularly when the data page is made of plastic, it is preferable to provide a hinge sheet and a core sheet provided on each side of the hinge sheet, and a laser marking sheet is further laminated on the surface of the core sheet. In addition, it is preferable that the passport has a protective sheet, and a protective sheet is further laminated on the surface of the laser marking sheet to protect the laser marking sheet. Specifically, a passport 10A consisting of laser marking sheet 1 / core sheet 2 / hinge sheet 3 / core sheet 2 / laser marking sheet 1 as shown in FIG. 2(a), or a passport 10B consisting of protective sheet 4 / laser marking sheet 1 / core sheet 2 / hinge sheet 3 / core sheet 2 / laser marking sheet 1 / protective sheet 4 as shown in FIG. 2(b) is preferable. Moreover, the laser marking sheet 1 may be omitted, and a card 10C may be used which is composed of protective sheet 4 / core sheet 2 / hinge sheet 3 / core sheet 2 / protective sheet 4 as shown in FIG. 2(c). In each of the passports 10A, 10B, and 10C, the layer configurations on both sides of the hinge sheet 3 are the same, but may be different on each side. For example, the core sheet 2, the laser marking sheet 1, and the protective sheet 4 may be provided in this order on one side of the hinge sheet 3, while the core sheet 2 and the marking sheet 1 may be provided in this order on the other side of the hinge sheet 3, with the protective sheet 4 omitted.

[0092] The laser marking sheet in the passport may have a dye-sublimation type thermal transfer image receiving layer as described above for the card. The passport may also have a sheet on which various information is stored in a storage medium such as an IC chip, that is, a so-called inlet sheet. The inlet sheet may be provided, for example, between the hinge sheet and the core sheet. The hinge sheet is a sheet that holds the recording layer, the core sheet, the inlet sheet, etc., and plays a role in firmly binding the cover of the passport together with other visa sheets, etc. Therefore, it is preferable that the hinge sheet has a strong heat fusion property, a suitable flexibility, heat resistance during the heat fusion process, etc.

[0093] The hinge sheet may be a known one, and may be a resin sheet made of a thermoplastic resin or a thermoplastic elastomer, such as a thermoplastic polyester resin, a thermoplastic polyester elastomer, a thermoplastic polyamide resin, a thermoplastic polyamide elastomer, a thermoplastic polyurethane resin, or a thermoplastic polyurethane elastomer, or may be made of a woven fabric, a knitted fabric, or a nonwoven fabric, or may be a composite material of a woven fabric, a knitted fabric, or a nonwoven fabric and a thermoplastic resin or a thermoplastic elastomer. The core sheet in the passport is the same as above, except that it is preferably 50 to 200 μm thick. The protective sheet in the passport is as described above. In the case of a passport, the core sheet, the laser marking sheet and the protective sheet are preferably laminated together in the above-mentioned layer structure and then pressed and heat-sealed. Alternatively, the sheets may be bonded together with an adhesive instead of heat-sealing.

[0094] At least one of the core sheet, laser marking sheet, and protective sheet provided on the card or passport may comprise the present film. By providing at least one of these sheets with the present film, it becomes easier to fuse the sheets together at low temperatures. In addition, since there is little dimensional change when heated, the workability during the manufacture of the card or passport is improved and warping of the card or passport can be prevented. Furthermore, the film has high impact resistance and is less likely to crack even after long-term use, thereby improving reliability during long-term use.

[0095] In cards or passports, the core sheet, the laser marking sheet, and the protective sheet may have a multi-layer structure as described above, and in that case, it is preferable that at least one layer is made of the present film. Also, it is preferable that the present film is arranged as the outermost layer of each sheet. Since the sheet having the present film arranged as the outermost layer is laminated to other sheets via the present film, it can be reliably fused to other sheets even by low-temperature heating.

[0096] In addition, in the card or passport, at least one resin layer constituting the core sheet, the laser marking sheet, and the protective sheet may be formed from the present film, and the other resin layers may not be formed from the present film. In such a case, the resin used for the other resin layer is not particularly limited as long as it is a thermoplastic resin, and examples thereof include polycarbonate resin, polyester resin, and mixtures thereof. EXAMPLES

[0097] Examples and comparative examples are shown below, but the present invention is not limited by these in any way.

[0098] The evaluation and measurement methods are as follows.

[0099] (1) Low temperature fusion properties Using a compression molding machine "NF-37" (manufactured by Shinto Metal Industries Co., Ltd.), the films (size 100 mm x 300 mm) obtained in each Example and Comparative Example were stacked and sandwiched between stainless steel plates, and the pressing pressure was 1.5 MPa, the pressing time was 5 minutes, and the subsequent cooling was performed for about 5 minutes until the film cooled down to room temperature, and heat fusion was performed. After that, the fused film was removed from the stainless steel plate, and the films were peeled off from each other to check whether the film was non-peeling (whether the material was broken). The heating temperature during pressing was increased in 10°C increments, and those that were non-peeling (those that had material broken) were judged to be fused, and the lowest temperature at which the film fused (material destruction temperature) was obtained. This material destruction temperature is the temperature at which the film is properly fused, and the lower the material destruction temperature, the better the low-temperature fusion properties.

[0100] (2) Solvent resistance At room temperature, a piece of film from each of the Examples and Comparative Examples was immersed in a petri dish containing a solvent for 1 minute, and the appearance was visually inspected and evaluated according to the following criteria. This test was carried out using ethyl acetate, toluene, and methyl ethyl ketone (MEK) as the solvent. OK: No change No: Melts

[0101] (3) Glass transition temperature (Tg) For each polyester resin used, a viscoelasticity spectrometer "DVA-200" (manufactured by IT Measurement & Control Co., Ltd.) was used to measure the temperature dispersion of dynamic viscoelasticity in accordance with JIS K7244-4:1999, at a strain of 0.07%, a frequency of 1 Hz, a heating rate of 3°C / min, and in tension mode. The temperature at the peak top of the loss modulus was determined as the glass transition temperature.

[0102] (4) Storage modulus A test piece of 4 mm×25 mm (thickness 100 μm) was cut out from the film obtained in each Example and Comparative Example to obtain a measurement sample. The measurement sample was used to measure the tensile storage modulus in MD at 90° C. using a viscoelasticity spectrometer "DVA-200 (manufactured by IT Measurement and Control Co., Ltd.)" in accordance with JIS K7244-4:1999, with a frequency of 1 Hz, a strain of 0.07%, and a temperature rise rate of 3° C. / min between -100 and 180° C.

[0103] (5) Heating expansion / contraction rate A test piece measuring 120 mm x 120 mm was cut out from the film obtained in each Example and Comparative Example, a standard line measuring 100 mm x 100 mm was marked in the center of the obtained test piece, and the test piece was heat-treated in an oven at 100°C for 10 minutes, and the standard line spacing in MD and TD before and after the treatment was used to calculate the distance from the standard line using the following formula. The standard line spacing was measured at the center of the standard line. Heat expansion rate (%) = [Standard line spacing after heat treatment (mm) - 100 (mm)] / 100 (mm) x 100 The closer the thermal expansion / contraction rate of a film is to 0, the better its heat resistance.

[0104] (6)Durability Eight sheets of the films obtained in each of the Examples and Comparative Examples were laminated so that the total thickness after heat pressing was about 800 μm, and then heat pressing was performed at a fusion temperature under the same conditions as in (1) Evaluation of low-temperature fusion properties to produce a laminate. A card measuring about 8.5 cm x about 5.4 cm was obtained by punching out the obtained laminate using a punching machine. The obtained card was set in a deflection tester, and a card bending test was performed in the short side direction under conditions of a deflection of 1 cm, a cycle of 0.5 Hz, and 30 times / min, with reference to JIS X6320:2009. The number of times the card was bent until cracks appeared was measured, and the results were evaluated according to the following criteria to serve as an index of durability. A: More than 50,000 times B: 30,000 to less than 50,000 times C: Less than 30,000 times

[0105] The raw materials used in the examples and comparative examples are as follows. (polyester resin) PCTG1: Copolymerized polyester resin (amorphous) of dicarboxylic acid consisting of terephthalic acid and dihydroxy compounds consisting of ethylene glycol (EG), 1,4-cyclohexanedimethanol (1,4-CHDM), and 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD), dihydroxy compounds (EG = 8 mol%, 1,4-CHDM = 74 mol%, TMCD = 18 mol%), recycled polyester resin recycled from scraps, glass transition temperature (Tg) = 100℃ PCTG2: Copolymerized polyester resin (amorphous) of dicarboxylic acid consisting of terephthalic acid and dihydroxy compound consisting of EG, 1,4-CHDM and TMCD, dihydroxy compound (EG = 2 mol%, 1,4-CHDM = 76 mol%, TMCD 21 mol%), recycled polyester resin recycled from scraps, glass transition temperature (Tg) = 104℃ PETG: A copolymer polyester resin (amorphous) of a dicarboxylic acid component consisting of terephthalic acid and a dihydroxy compound consisting of EG and 1,4-CHDM, dihydroxy compound (EG = 70 mol%, 1,4-CHDM = 30 mol%), glass transition temperature 78℃ (Polycarbonate resin) PC: Sumitomo Polycarbonate "Caliber 301-4" (Additives) Lubricant 1: Polyethylene glycol (number average molecular weight 3000): sodium dodecylbenzenesulfonate = 2:1 (mass ratio) Lubricant 2: A mixture of Montan acid ester wax and fluoropolymer Impact resistance improver 1: Core-shell type elastomer, Kaneka Corporation's "Kane Ace M-300", methyl methacrylate-butadiene-styrene copolymer (MBS) Impact resistance improver 2: Core-shell type elastomer, Mitsubishi Chemical's "Metablen S-2001", Core: Silicone-acrylic composite rubber

[0106] [Examples 1 to 4] According to the formulation shown in Table 1, the resin, or the resin and additives, were charged into a twin-screw extruder and kneaded, and the resin composition was extruded at 240° C. using the twin-screw extruder to obtain a film having a thickness of 100 μm.

[0107] [Comparative Example 1] The same procedure as in Example 1 was carried out except that the composition was changed as shown in Table 1 and the extrusion temperature was changed from 240°C to 250°C.

[0108] [Comparative Examples 2 and 4] The same procedure as in Example 1 was carried out except that the composition was changed as shown in Table 1 and the extrusion temperature was changed from 240°C to 230°C. [Comparative Example 3] The same procedure as in Example 1 was carried out except that the composition was changed as shown in Table 1 and the extrusion temperature was changed from 240°C to 270°C.

[0109] [Table 1]

[0110] As shown in Table 1, the resin compositions of Examples 1 to 4 contain a polyester resin (A) having a glass transition temperature of 90° C. or higher and an impact resistance improver, and thus have excellent low-temperature fusion properties and solvent resistance. In addition, the storage modulus at 90° C. was high and the heat resistance was excellent, so the thermal expansion rate was close to 0%, and the thermal expansion rate value was low. Therefore, it can be understood that when using this resin composition to manufacture a card or passport, the size change during thermal processing is small, workability is high, and the occurrence of warping can be suppressed. In addition, despite the use of polyester resin, no cracks were observed for a long period of time in the card bending test, and durability was equivalent to or greater than that of Comparative Example 3, which used polycarbonate resin, and reliability in long-term use was also high.

[0111] On the other hand, the resin compositions of Comparative Examples 1 and 2 contained a polyester resin but no impact modifier, and therefore cracks appeared early in the card bending test, and durability was insufficient. In Comparative Example 3, since a polycarbonate resin was used, the solvent resistance and low-temperature fusion properties were not good. In Comparative Example 4, since PETG with a low glass transition temperature was used, the low-temperature fusion property was good, but the solvent resistance and heat resistance were not good. In addition, compared with Examples 1 and 2, which used polyester resin (A) with a high glass transition temperature, the content of the impact resistance modifier was at the same level, but the durability was low. This is thought to be because the resin compositions of Examples 1 and 2 contained polyester resin (A) in addition to the impact resistance modifier, which improved the impact resistance and therefore further improved the durability. In addition, Comparative Examples 2 and 4 have excellent low-temperature fusion properties, and when the films of Comparative Example 2 and Comparative Example 4 are fused together at low temperatures, size change is suppressed and workability is good, but only cards or passports with low heat resistance are obtained. On the other hand, when the film of Comparative Example 2 or Comparative Example 4 is fused to a film with high heat resistance (e.g., a polycarbonate film) to increase the heat resistance of the card or passport, it is necessary to increase the fusion temperature, but if the fusion temperature is high, size change occurs in the films of Comparative Examples 2 and 4, workability decreases, and warping occurs. In other words, it can be understood that when the resin compositions of Comparative Examples 2 and 4 are used, it is difficult to achieve the effect of the present invention regarding heat resistance, even when combined with other films.

[0112] 1 Laser marking sheet 2 Core sheet 3 Hinge Sheet 4 Protective sheet 20A, 20B, 20C Cards 10A, 10B, 10C Passport

Claims

1. A resin composition containing a resin component including a polyester resin (A) and an impact resistance improver, The glass transition temperature of the polyester resin (A) is 90° C. or higher, the polyester resin (A) contains a structural unit derived from a chain dihydroxy compound and a structural unit derived from an alicyclic dihydroxy compound, the polyester resin (A) comprises a polyester resin in which the proportion of the structural units derived from the alicyclic dihydroxy compound is more than 65 mol % relative to a total of 100 mol % of the structural units derived from the chain dihydroxy compound and the structural units derived from the alicyclic dihydroxy compound, The resin component includes a polyester resin (B) other than the polyester resin (A), the polyester resin (B) contains a structural unit derived from a chain dihydroxy compound and a structural unit derived from an alicyclic dihydroxy compound, The glass transition temperature (Tg) of the polyester resin (B) is less than 90° C., The polyester resin (B) is a resin composition for cards or passports, in which the proportion of structural units derived from an alicyclic dihydroxy compound is 65 mol % or less out of a total of 100 mol % of structural units derived from a chain dihydroxy compound and structural units derived from an alicyclic dihydroxy compound.

2. Storage modulus at 90°C is 3 x 10 7 The resin composition for cards or passports according to claim 1, wherein the viscosity of the resin composition is 100 Pa or more.

3. 3. The resin composition for cards or passports according to claim 1, wherein the polyester resin (A) contains a structural unit derived from ethylene glycol and a structural unit derived from cyclohexanedimethanol.

4. The resin composition for cards or passports according to any one of claims 1 to 3, wherein the polyester resin (A) contains a structural unit derived from ethylene glycol, a structural unit derived from cyclohexanedimethanol, and a structural unit derived from tetramethylcyclobutanediol.

5. A resin composition for cards or passports described in any one of claims 1 to 4, wherein the glass transition temperature (Tg) of the polyester resin (B) is 88°C or lower.

6. 6. The resin composition for cards or passports according to claim 1, wherein the impact resistance improver is a core-shell type elastomer.

7. 7. The resin composition for cards or passports according to claim 6, wherein the core of the core-shell type elastomer comprises at least one rubber selected from the group consisting of butadiene-based rubber, acrylic-based rubber, silicone-based rubber, and silicone-acrylic composite rubber.

8. The resin composition for cards or passports according to any one of claims 1 to 7, wherein the content of the impact resistance improver is 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the resin component.

9. The resin composition for cards or passports according to any one of claims 1 to 8, comprising recycled raw materials.

10. A card or passport film comprising the resin composition according to any one of claims 1 to 9.

11. A card comprising the film of claim 10.

12. A passport comprising the film of claim 10.

13. A method for producing a resin composition according to any one of claims 1 to 9, comprising blending a recycled raw material into the resin composition.

Citation Information

Patent Citations

  • Thermoplastic resin composition and sheet or card made therefrom

    JP1999001607A

  • Resin composition for card

    JP1999189708A

  • Heat-resistant card

    JP2003118056A

  • Laminate, and card, tag and label using the same

    JP2003191415A

  • Polylactic acid-based resin composition, molded article using the same and manufacturing method

    JP2007246694A